The use of innovative technologies in the production of culinary products in public catering enterprises - E. S. Franchenko; M. Yu. Tamova; T. A. Dzhum; R. A. Zhuravlev; K. K. Nikanov (Новые технологии, 2023)
The article investigates the use of non-traditional ingredients and the use of innovative processing methods in the production of preventive products. The relevance of the research lies in the fact that currently the importance of the treatment of pathological diseases such as iron deficiency anemia, accompanied by a low level of hemoglobin and red blood cells in the circulating blood and is characterized by impaired oxygen transport and the development of hypoxia, is increasing. The article provides an overview of the types of raw materials containing increased amounts of digestible iron, and describes modern technologies for the production of culinary products for people suffering from anemia. The purpose of the research is to expand the range of specialized culinary products – homogeneous products made from raw meat that meet the concept of healthy nutrition. The main tasks include justification of the choice of recipe ingredients, innovative technology for the preparation of liver pate with high biological and nutritional value, developing a recipe and studying consumer properties and safety indicators. The object of the research is beef liver pate with pine nuts, obtained using innovative sous vide technology. Experimental studies have been carried out at the Department of Public Nutrition and Service of Kuban State Technical University on the qualitative characteristics of raw meat and offal (liver), which have the highest content of iron, pine nuts, in order to confirm the prospects of their use for the development of a recipe composition that allows replacing animal fats with vegetable fats, which has a positive effect on the calorie content and chemical composition of a dish. Methods for preparing pates have been analyzed, based on the identified shortcomings, and the authors have proposed temperature-time regimes for low-temperature heat treatment to reduce the loss of nutrients. Organoleptic, microbiological and physical and chemical quality indicators of the developed pate have been determined. Conclusions: to prevent iron deficiency anemia, it is necessary to develop products not only rich in iron, but also with the vitamin, fatty acid (ω-3 and ω-6 acids) and amino acid composition with which iron is better absorbed, to use innovative processing methods to reduce the loss of beneficial substances.